The child and the family in frames of activities of Barnavernet organization. An attempt of evaluation from the Polish and Norwegian perspective - Elżbieta Czykwin (Studia z Teorii Wychowania)
In the article, the author raises controversial questions concerning the functioning of the Norwegian institution Barnavernet, seen from both Polish and Norwegian perspectives. A diplomatic conflict, in which the Norwegian representatives recognized the Polish consul Sławomir Kowalski as persona non grata in Norway, constitutes a pretext for discussion. The main thesis of the article is the indication of the different and deep mental characteristics of Poles and Norwegians, which determine the image and evaluation of the institution’s functioning. It is constituted by: (1) the trust, especially bridging trust, significantly low in Poland and very high in Norway; (2) the very Polish “culture of complaining” staying in opposition to affirmativeness of Norwegians; (3) the act of giving more significance to the country while solving the family conflicts in Norway and leaving those conflict, especially the issues concerning children, in the area of responsibility of the family only; (4) mentality based and built on tradition and the past in Poland and the orientation directed towards the future in Norway; (5) high level of social consent to violence in Poland in opposition to Norway, where violence is additionally seen in more sophisticated and differentiated way. The latest research of brain physiologists concerning experiencing violence and fear by the child, especially in the early period of its life proves that the changes in the child’s brain have destructive, and what is even more important, permanent effect. In some way, this fact reinforces the practice of taking away children from their biological families. On the other hand, the trauma of being taken away is not noticed by the Norwegians. In a sense, the diplomatic conflict resulting in expulsion of the Polish consul from Norway can begin the freshening corrections in the functioning of this institution.